Pemaknaan Proses Afiksasi Verba dalam Berita News UAD: Tinjauan Morfologi dan Korpus Data (The Semantic Interpretation of Verbal Affixation Processes in UAD News: A Morphological and Corpus Data Review) - Bagus Prakoso; Mafatihul Hidayah (Universitas Sebelas Maret, 2025)
This study examines the meaning of verb affixation processes in news articles published by News UAD, with a focus on the affixation present in the verb word class. The main objectives of this study are (1) to define the meaning of verb affixation in News UAD articles, (2) to describe the meaning of verb affixation in News UAD articles, and (3) to highlight the dominant meanings of verb affixation most commonly found in News UAD articles. The data used consists of articles published between August 9, 2024, and October 15, 2024. The analysis results indicate that affixation on verbs attaches to four main meanings: performing an activity, or having someone else perform an action, producing, and making something. The prefix ber- tends to convey the meaning of performing an activity, while the prefixes me- and its variants men- and meng- are more dominant in conveying the meaning of performing an action for someone else or intending to do something. The circumfixes me-kan and meng-kan function to form the meaning of making something happen. This affixation process also often involves a change in word class from nouns to verbs. These findings show that the use of verb affixation in News UAD emphasizes news focusing on the processes or actions involved in various activities and events. The results not only highlight the dominance of verb affixation in News UAD but also reveal the presence of derivation, inflection, and allomorphs or sound variations.